ANALISIS KETERAMPILAN JUMPING SMASH BULUTANGKIS PADA ATLET PBSI SAROLANGUN - Rafizki Mubarak; Boy Indrayana; Anggarawan Janur Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the jumping smash skills of athletes from the Indonesian Badminton Association (Badminton Indonesia) in Sarolangun Regency. The jumping smash is an offensive technique in badminton that plays a crucial role in scoring points, making mastery of this technique a determining factor in an athlete's success in a match.The method used in this study was descriptive quantitative, with observation and skills testing approaches. The subjects were PBSI Sarolangun athletes who actively participated in training and competitions. The research instruments included jumping smash ability tests, technique observations, and analysis of movement components, including the approach, takeoff, body position in the air, shuttlecock contact, and landing.The results showed that the athletes' jumping smash skills were in the fair to good category. However, several deficiencies were identified, particularly in the aspects of movement coordination and push-off power. Factors influencing these skills include physical condition, mastery of basic techniques, and training intensity.The conclusion of this study indicates that the jumping smash skills of PBSI Sarolangun athletes still need to be improved through a more structured and specific training program, particularly in developing leg muscle strength and movement coordination. This research is expected to serve as a reference for coaches in developing training programs to improve athlete performance.